PENGARUH PROFESIONALISME, SENSITIVITAS ETIS, DAN REWARD TERHADAP INTENSI AUDITOR INSPEKTORAT BADUNG DALAM MELAKUKAN WHISTLEBLOWING INTERNAL - Dewi, Ni Ketut Meyta Pradnya; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024DO - 10.24843/EEB.2024.v13.i06.p18, 2024)
This research aims to evaluate the influence of professionalism, negatively impactful ethical sensitivity, and rewards on the internal whistleblowing intentions of auditors in the Badung Inspectorate. The study was conducted using questionnaires distributed to 47 auditors in the Badung Inspectorate. The study's findings indicate that professionalism and ethical sensitivity has a positive impact on the auditor's intention to participate in internal whistleblowing, while rewards were found to have no impact on auditor intentions. These findings can provide valuable insights for governments and supervisory bodies to enhance internal whistleblowing and improve financial and operational governance. Based on the test results, the whistleblowing intention variable is still influenced by other factors, 15.7 percent of which is explained by other variables not included in the research model. Therefore, it is recommended for future researchers to refine and develop this research by adding variables which are other factors that can explain whistleblowing intentions such as disclosure of fraud at the APIP, the auditor's understanding of investigative audits, the independence and steptism of an APIP, experience, personal costs. , professional commitment, and loss of control.